Dukungan Keluarga dan Kecemasan Pada Klien Diabetes Melitus - Arma Vica Hulandari; Dwi Retno Sulistyaningsih (STIKes Ibnu Sina Ajibarang, 2025)
Diabetes melitus is a degenerative disease that increase every year and it is at risk of having serious complications that can cause anxiety. Family support is an important factor when a person had a healthy problem as a preventive effort to reduce anxiety. This research purpose to know the relation between family support and anxiety to the patients with diabetes melitus. This research applies cross sectional design. The populations in this research are patients with diabetes melitus at periuk jaya primary health center. The sampling technique used total sampling according to inclusion criteria as many as 43 respondents. The data were collected by using questionnaires. Analyzed by chi square. The result of the research showed that a small percentage of people with diabetes melitus who had anxiety were 2 people (4.7%) and those who did not get family support were 18 people (41,9%). Statistic test result with significance P=0.169, showed that P-value is bigger than 0.05 (0.169>0.05). In conclution the result showed that family support is not related with anxiety on patients with diabetes miletus. The significance result of this research showed that family support did not affect anxiety. It becomes a basic that family support is not one of the factors that affect anxiety. Therefore, hopefully health workers can pay attention to psychosocial needs, especially to the patients with diabetes melitus. Key words: Anxiety, Family support, Diabetes melitus. Diabetes melitus merupakan penyakit degeneratif yang mengalami peningkatan setiap tahunnya dan beresiko memiliki komplikasi serius sehingga bisa menimbulkan kecemasan. Dukungan keluarga merupakan faktor penting ketika seseorang mengalami masalah kesehatan, sebagai upaya preventif untuk mengurangi cemas. Penelitian ini bertujuan untuk mengetahui adakah hubungan dukungan keluarga dengan kecemasan pada klien diabetes melitus. Penelitian ini menggunakan desain cross sectional. Populasi dalam penelitian ini klien diabetes melitus di Puskesmas Periuk Jaya. Teknik sampling menggunakan total sampling sesuai dengan kriteria inklusi sebanyak 43 responden. Pengumpulan data menggunakan kuesioner. Analisa dilakukan menggunakan uji chi square. Hasil penelitian sebagian kecil klien diabetes melitus yang mengalami kecemasan yaitu 2 orang (4.7%) dan yang tidak memiliki dukungan keluarga yaitu 18 orang (41.9%). Hasil uji statistik diperoleh dengan nilai signifikasi p-0.169, yang menunjukkan nilai p-value lebih besar dari 0.05 (0.169 > 0.05). Dari hasil tersebut disimpulkan bahwa tidak ada hubungan antara dukungan keluarga dengan kecemasan pada klien diabetes melitus. Hasil yang signifikasi penelitian ini menunjukkan dukungan keluarga tidak mempengaruhi kecemasan. Ini menjadi dasar bahwa dukungan keluarga adalah bukan salah satu faktor yang mempengaruhi kecemasan. Dengan ini, diharapkan petugas kesehatan dapat memperhatikan kebutuhan tentang psikososial khususnya pada klien diabetes melitus. Kata kunci: Kecemasan, Dukungan keluarga, Diabetes melitus.